Risk Factors in Post Operative Wound Infections Following Elective Abdominal Operations - Akramuzzaman, S M; Islam, Md Sherajul; Galib, Asadullahil (Medicine Today, 2023)
Introduction: Surgical site infections are common post operative complication and cause significant post operative morbidity and mortality, and have serious consequences for outcomes and costs. Different risk factors are involved, including age, sex, smoking, nutrition, diabetes, pre existing illness, pre operative hospital stay time, pre operative shaving, level of surgeon, length of incision, duration of operation, per operative blood transfusion, wound drainage and nature of wound. The objective of this study was to determine the risk factors affecting abdominal surgical site infections and their rate at Dhaka Medical College & Hospital, a major referral teaching hospital in Bangladesh. Objectives: were to identify risk factors in post operative wound infections following elective abdominal surgery. Materials and Methods: A Cross sectional type of observation study was carried out among 153 patients in Department of Surgery, Dhaka Medical College Hospital, Dhaka from January 2008 to December 2009. Results: Patients (n = 153) who had undergone elective surgery were studied and the relationships among variables were analyzed by Student's t and Chi-square tests. To test the independence of the risk factors, the significant variables (p _.05) in the univariate analyses were entered into a stepwise logistic regression equation. Data were collected through pre and postoperative examinations. The subjects were followed till discharge. Of the 153 patients, 13 suffered from SSI (8.5%). Among the infections superficial SSI was in 8 cases (61.54%), deep SSI in 3 cases (23.08%), and organ/space SSI in 2 (15.38%) cases. There were 14 different variables in study to determine the risk factors. In univariate analysis ten risk factors were identified: age, underweight, diabetes, ASA score, pre operative hospital stay, per operative blood transfusion, length of incision, duration of operation, wound drain and contaminated wound. And in multivariate analysis duration of operation, diabetes mellitus and ASA score appeared to be independent risk factors for wound infection. Conclusion: The total elimination of wound infection is not possible, a reduction in the infection rate to a minimal level could have significant benefits in terms of both patient comfort and medical resources used. The SSI may be reduced to a more acceptable level by reducing the average operation time to less than 2 hours, pre operative hospital stay, and by reducing contamination during operation and wound drainage. Furthermore post operative study in large scale is recommended. Medicine Today 2023 Vol.35(1): 56-62